A moral cleansing process how and when does unethical pro-organizational behavior increase prohibitive and promotive voice - Wang, Ying; Xiao, Shufeng; Ren, Run (2022)
In this study, we draw on moral cleansing theory to investigate the consequence of unethical pro-organizational behavior (UPB) from the perspective of the actors. Specifically, we hypothesize that after conducting UPB, people may feel guilty and tend to cleanse their wrongdoings by providing suggestions or identifying problems at work (i.e., prohibitive and promotive voice). We further hypothesize that the above relationship is moderated by the actor’s moral identity symbolization. We conducted three studies, including experiment and surveys, to test our hypotheses. Results of these studies show consist-ent support to our hypotheses. In particular, individuals reported more felt guilt after conducting UPB, and they tended to compensate with more prohibitive and promotive voice subsequently. In addition, the indirect relationship from UPB acting to both voice behaviors via felt guilt was stronger for people with a high level of moral identity symbolization. Theoretical and practical implications are discussed.
Keywords: Unethical pro-organizational behavior (UPB); Moral cleansing theory; Felt guilt; Prohibitive and promotive voice; Moral identity symbolization (MIS); Aufsatz in Zeitschrift